UMP makes country proud, 22 academicians among worlds top scientists - T.N., Alagesh (New Straits Times Press (M) Bhd., 2022)
KUANTAN: Twenty-two Universiti Malaysia Pahang (UMP) lecturers have made the institution proud after they were ranked among the world's "Top 2% Scientist" in the list of outstanding researchers in various fields and disciplines released by United States-based Stanford University.